Tuberculosis: Studies on Role of Gender, Age and Drug Addiction in Eastern Part of India (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2011)
Objectives: The objective of the present investigation was to determine the socioeconomic conditions, age and gender relations to tuberculosis with evaluation of drug (smoking/ alcohol) influences on it and correlate the clinical data to an animal experiment result of antioxidant system of drug treated male rats. Settings: The investigation was carried out in a rural and an urban part of Eastern India. Methodology: Acid-fast bacillus (AFB) staining of sputum was performed in rural Indpur (total human individuals 498, male 384) and urban area Kamarhati (total 1017, male 735) following WHO guidelines. Catalase, superoxide dismutase (SOD) activities and level of non-protein soluble thiol (NPSH), malondialdehyde (MDA) were measured in lung of rats exposed four weeks to nicotine (0.2 mg/kg s.c.) and/or ethanol (20% [w/v] at 3 g/kg orally). Results: Mean AFB score was greater in all age groups of Kamarhati. Smoking/ alcohol alone significantly and synergistically even in greater extent increased TB severity in both places, furthering it in backward classes. Drug treatment significantly increased MDA level and SOD activity with a decrease in NPSH level and catalase activity in rat. Conclusions: Males are greater sensitive to TB and urban area is affected more. Clinical findings paralleled with animal experiments pointing the disastrous consequences of nicotine. Up-gradation of socioeconomics in rural area, avoiding of reckless unscientific changes of demographic profile of a region, and minimization of pollutions in urban areas may diminish disease outbreak. Key words: Tuberculosis; Rural and urban; Risk factors; Antioxidant systems; Rat lung DOI: 10.3126/saarctb.v7i2.4398SAARC J. TUBER. LUNG DIS. HIV/AIDS 2010 VII(2) 1-9